Hubungan Desain Stasiun Kerja dan Postur Kerja Dengan Keluhan Musculoskeletal Disorders Pekerja Pelayanan Publik di Karanganyar - Nurvita Eka Rizky; Bachtiar Chahyadhi; Isna Qadrijati (Sekolah Vokasi, Universitas Sebelas Maret, 2024)
A recent analysis of the 2019 Global Burden of Disease (GBD) data shows that approximately 1.71billion people worldwide are living with musculoskeletal disorders (MSDs). Office work has the potential to cause musculoskeletal disorders (MSDs), as office work is characterized by monotonous and repetitive movements for long periods of time and work with static postures. The urgency of thisstudy is to obtain an overview of the relationship between workstation design and work posture with complaints of musculoskeletal disorders. This research method is analytical observational research with cross-sectional approach. This research was conducted in Karanganyar Public Service Mall in 2023. The study population was Karanganyar Public Service Mall workers with a total of 48 workers. The sampling technique was total population technique. Musculoskeletal complaints were measured using the Nordic Body Map questionnaire, while workstation design was measured using a measuring device and work posture was measured using the Rapid Upper Limb Assessment (RULA) method. The results showed that there was a significant relationship between work posture and musculoskeletal complaints with a pvalue = 0.037 and a correlation coefficient or r of 0.285